Chikungunya virus: An emerging public health challenge for Pakistan (Journal of Fatima Jinnah Medical University, 2022)
Chikungunya is a viral illness caused by the Chikungunya virus (CHIKV), an enveloped single-stranded linear RNA alphavirus belonging to the family Togaviridae. The CHIKV is transmitted by the same Aedes mosquito (Ae. aegypti and Ae. albopictus) responsible for transmitting the dengue and Zika viruses to humans.1 These viruses can co-circulate in an area and concurrent infections are possible in the same person.1Chikungunya is a viral illness caused by the Chikungunya virus (CHIKV), an enveloped single-stranded linear RNA alphavirus belonging to the family Togaviridae. The CHIKV is transmitted by the same Aedes mosquito (Ae. aegypti and Ae. albopictus) responsible for transmitting the dengue and Zika viruses to humans.1 These viruses can co-circulate in an area and concurrent infections are possible in the same person.1CHIKV infections are mostly symptomatic (~80%), and the symptoms are similar to dengue virus infection, with fever and polyarthralgia being the commonest. The Chikungunya fever can be divided into three stages: acute (1-21 days), post-acute (22 to 90 days), and chronic stages (>90 days).2 However, post-acute and chronic stages are not observed in all patients.3 The acute stage starts after a very brief incubation period (average 3 days, range 1-12 days) with typical symptoms including high-grade fever (>38.5oC), arthralgia, arthritis with edema and pain, myalgia, headache, a maculopapular rash with cutaneous pruritus (soles and palms), facial edema, and lymphadenopathy. The infection is associated with mild thrombocytopenia, increased levels of liver enzymes, increased C-reactive protein (~50–60 mg/L), and lymphopenia (
Keywords: Vector-borne diseases; Chikungunya; Aedes aegypti; Public health; Mystery disease